Periodic current oscillations at the gold/acid aqueous interfaces induced by HCl additions - Podestá, José J. (1979)
The periodic oscillating current recorded under a constant potential step for Au/acid solution interfaces containing different concentrations of Cl− ion is studied in the 25–50°C range. Two main electrochemical reactions coupled to two diffusion processes are responsible for the periodic effect. The electrochemical reactions occurring successively are the electrodissolution of gold as the AuCl−2 complex, a reaction which is diffusion controlled and then the oxide layer formation when the solution is depleted of Cl− ion. Subsequently, as the anodic current decreases due to the electrode passivation, the HCl diffuses backwards and dissolves the oxide film. The active part of the periodic cycle is interpreted in terms of a diffusional process involving at its initiation the simultaneous uncoverage of the electrode surface.